Implementation of Blue Economy to Increase Lobster Production through Natural Feeding Efficiency - Achmad, Dewi Shinta; Akbar, Muh. Firyal; Ardiansyah, Widiastuti; Mokoolang, Susan; Tusaban, Tusaban (Journal of Universal Community Empowerment Provision, 2024)
Community Service Activities entitled Freshwater Lobster and Silkworm Cultivation, were carried out from September to November 2024. The need for freshwater lobster feed that is difficult to obtain makes natural feed such as silkworm cultivation, an alternative to be used as feed for freshwater lobster cultivation. In addition, Freshwater Lobster cultivation is still very rarely carried out in the Gorontalo area, thus providing opportunities and benefits for inmates to be able to become independent after leaving prison. The need for freshwater lobster feed that is difficult to obtain makes natural feed for larvae/fry such as silkworms, an alternative to be used as feed for freshwater lobster cultivation. This PKM activity is a new hope for inmates to get a sustainable livelihood and income.